2023
DOI: 10.3390/agronomy13071840
|View full text |Cite
|
Sign up to set email alerts
|

Response of Rice Grain Yield and Soil Fertility to Fertilization Management under Three Rice-Based Cropping Systems in Reclaimed Soil

Abstract: Reasonable cropping systems and fertilizer management are vital for improving the quality of barren soil. The effectiveness of different crop rotation methods and fertilizers in soil improvement depends on various factors, including soil type, climate conditions, and crop type. In the present study, based on three rice-based cropping systems, the effects of organic fertilizers combined with slow-release fertilizers on rice yield and soil fertility in reclaimed soil were analyzed. The results showed that the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…A recent study also showed that NPK applied by drip fertigation may enhance chrysanthemum inflorescence characteristics, such as yield, biochemical activity, and soil nutrient status [8]. In other studies, potassium increased stalk thickness [12], and organic fertilizer promoted growth and improved crop quality [13]. Similarly, nitrogen, phosphorus, and potassium, through with different ratios of use, prompt plant mass efficiency [14].…”
Section: Introductionmentioning
confidence: 95%
“…A recent study also showed that NPK applied by drip fertigation may enhance chrysanthemum inflorescence characteristics, such as yield, biochemical activity, and soil nutrient status [8]. In other studies, potassium increased stalk thickness [12], and organic fertilizer promoted growth and improved crop quality [13]. Similarly, nitrogen, phosphorus, and potassium, through with different ratios of use, prompt plant mass efficiency [14].…”
Section: Introductionmentioning
confidence: 95%